Analysis of the usability of graphical interfaces of car rental websites with consideration of universal design principles - Szewczyk, Jakub; Skublewska-Paszkowska, Maria (Journal of Computer Sciences Institute, 2024)
The study presents an analysis of two versions of a car rental website’s graphical interface in terms of usability and accessibility. a literature review was conducted to clarify concepts such as universal design, usability, and user experience. Two types of the car rental website were developed: one adhering to universal design principles and the other not considering these principles. The research employed tools such as WAVE, surveys, the LUT checklist, and an eye tracker. Metrics like time to first fixation and user ratings were analyzed. The experiments demonstrated that the website following universal design principles is more intuitive and user-friendly. Heatmaps and gaze paths illustrate that the version developed according to universal design principles significantly facilitates users in finding the information they need. Survey results proved that users rate websites developed according to universal design principles significantly